Flowable resin used as a sealant in molars using conventional, enameloplasty and fissurotomy techniques: An in vitro study - Chaitra, TR; Subba Reddy, VV; Devarasa, GM; Ravishankar, TL (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2010)
Preventive procedures using pit and fissure sealants are one of the most important aspects of pediatric dental practice. The objectives of this in vitro study were to comparatively evaluate microleakage of a flowable resin used as a sealant on molars after preparation with conventional, enameloplasty and fissurotomy techniques. A total of 24 teeth were divided into three groups of eight samples each. Pits and fissures were prepared with conventional sealant technique (CST) (Group A), enameloplasty sealant technique (EST) (Group B) and fissurotomy technique (FT) (Group C). Following sealant placement, thermocycling and sectioning of samples of Groups A, B and C were performed and microleakage was assessed under a stereomicroscope after methylene blue dye immersion. There was significantly lesser microleakage in EST when compared with CST and FT, which showed more microleakage. No statistical significance between CST and FT was found. EST has proven to be an excellent method of preparation of pits and fissures when flowable composite is used as a sealant because of its lesser microleakage.